Signet-ring cells in the bone marrow as an indication of cryptic metastasis of breast carcinoma: A case report. Issue 11 (March 2019) - Ma, Shuang; Jr, Bruce D. Leckey; Zhang, Wan-Lin; Xu, Hong-Tao; Yang, Lian-He; Wang, Endi
Abstract: Rationale: Signet-ring cell is a rare morphological finding in bone marrow, which usually indicates metastatic carcinoma from either the gastrointestinal tract or a primary hematolymphoid neoplasm. Here, we present a very unusual case of lobular breast carcinoma with metastasis to the bone marrow. Patient concerns: A 67-year-old female with estrogen receptor (ER)-positive lobular breast carcinoma was staged as T3N3M0, and treated with modified radical mastectomy followed by chemotherapy and radiotherapy. One year after treatment, she was noted to have moderate thrombocytopenia on complete blood count with the remainder of the parameters within normal limits. Radiographic examination revealed no evidence of recurrent disease. Diagnosis: Bone marrow biopsy was performed to exclude therapy-related myelodysplastic syndrome (MDS), which demonstrated hypercellularity with "hyperplastic" hematopoiesis. Upon closer inspection, a few signet-ring cells were identified which morphologically resembled histiocytes. These formed an interstitial infiltrate among the predominantly hematopoietic elements, and could have been easily overlooked. Immunohistochemistry demonstrated that these signet-ring cells were positive for pancytokeratin as well as ER which confirmed metastatic lobular breast carcinoma. On retrospective review of the aspirate smear, rare signet-ring cells were identified. Interventions: The patient was treated with additional chemotherapy. Outcomes: The patient eventually succumbed to overt dissemination after 14 months. Lessons: Due to the relative discohesiveness of lobular breast carcinoma, the cells frequently assume single-cell infiltration in bone marrow. This attribute, along with small cell size, bland cytologic features and paucity of tissue response, contributes to its escaping from identification on hematoxylin-eosin (H&E) sections. In this case, the signet-ring cells were hidden in apparently hyperplastic hematopoiesis. Careful inspection raised the possibility of occult metastasis which was readily detected and confirmed with immunohistochemistry.